Lithium ion battery
By adding solid electrolyte to the positive electrode sheet of the lithium-ion battery and adding the first additive to the electrolyte, the median particle size D50 of the electrolyte is adjusted, and the performance problems of lithium-ion battery in low and high temperature environments are solved, and the electricity is achieved The core has good low-temperature discharge performance and high-temperature cycle life.
Patent Information
- Application Number
- CN202411911338.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-02-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The battery polarization phenomenon of lithium-ion batteries worsens in low-temperature environments, resulting in the battery cell voltage reaching the cutoff voltage ahead of schedule, the discharge capacity is reduced, and even the discharge cannot be discharged, and the circulation performance deteriorates in high-temperature environments.
By adding solid electrolyte to the positive electrode sheet and adding a first additive to the electrolyte, a protective film is formed to reduce side reactions, and the median particle size D50 of the solid electrolyte is adjusted to satisfy 1.25≤L/(D*S)≤5 The conditions ensure that the performance of lithium-ion batteries in low and high temperature environments are taken into account.
It effectively improves the high-temperature service life of the battery cell and reduces polarization at low temperatures, ensuring both the low-temperature discharge performance and high-temperature cycle life of lithium-ion batteries.
Smart Images

Figure CN119400963A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and in particular relates to a lithium ion battery. Background Art
[0002] In low temperature environment (≤0℃), the polarization phenomenon of lithium-ion batteries increases, causing the cell voltage to reach the cut-off voltage in advance, resulting in a decrease in discharge capacity or even failure to discharge. The key to improving this problem lies in increasing the transfer rate of lithium ions between materials, electrolytes and the interface between materials and electrolytes under low temperature conditions.
[0003] By adding lithium ion fast conductors to the materials and optimizing the electrolyte formula, the transmission rate of lithium ions in the materials, the interface between the materials and the electrolyte, and the electrolyte can be effectively improved to reduce the polarization of the battery cell. However, after the polarization of the battery cell is reduced, the gram capacity of the positive electrode material in a high temperature environment will also increase, which will worsen the cycle of the battery cell in a high temperature environment. In addition, if the amount of conventional positive electrode protection additives such as nitrile additives or sulfonate additives is increased to increase the cycle life of the battery cell, the impedance of the positive electrode material will be worsened and the viscosity of the electrolyte will be increased, thereby worsening the low-temperature rate performance of the battery cell. Therefore, how to make lithium-ion batteries have both good performance in low-temperature environments and high-temperature service life has become an urgent problem to be solved. Summary of the invention
[0004] Aiming at the problem in the prior art that it is difficult to balance high rate discharge and high temperature cycle performance of lithium ion batteries in a low temperature environment, a lithium ion battery is provided.
[0005] The technical solution adopted by the present invention to solve the above technical problems is as follows: In one aspect, the present invention provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the positive electrode sheet comprises a positive electrode material layer, the positive electrode material layer comprises a positive electrode active material and a solid electrolyte, and the electrolyte comprises a first additive; The first additive comprises at least one of the following compounds: ; The lithium-ion battery meets the following conditions: 1.25≤L / (D*S)≤5; S% is the mass percentage of the first additive in the electrolyte; L% is the mass percentage of the solid electrolyte in the positive electrode material layer; Dμm is the median particle size D50 of the solid electrolyte in the positive electrode material layer.
[0006] Optionally, the solid electrolyte includes one or more of lithium aluminum titanium phosphate, lithium lanthanum titanium oxide and lithium lanthanum zirconium oxide.
[0007] Optionally, the mass percentage of the solid electrolyte in the positive electrode material layer is 0.5%-2%.
[0008] Optionally, based on the total mass of the electrolyte being 100%, the mass percentage of the first additive is 1%-4%.
[0009] Optionally, the median particle size D50 of the solid electrolyte in the positive electrode material layer is 0.4-0.7 μm.
[0010] Optionally, the electrolyte further comprises a lithium salt and an organic solvent; Based on the total mass of the electrolyte being 100%, the mass percentage of the lithium salt is 12%-18%; Taking the total mass of the electrolyte as 100%, the mass percentage of the organic solvent is 59.5%-71.9%.
[0011] Optionally, the lithium salt includes one or more of lithium hexafluorophosphate, lithium difluorophosphate, lithium tetrafluoroborate, lithium bisfluorooxalatoborate, lithium bisoxalatoborate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethylimide, lithium difluorooxalatophosphate, lithium perchlorate and lithium nitrate; and / or, the organic solvent includes two or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl formate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate and ethyl difluoroacetate.
[0012] Optionally, the electrolyte further includes a second additive, wherein the second additive includes one or more of n-butyl phosphoric anhydride, lithium tetrafluoroborate and lithium difluorophosphate; Based on the total mass of the electrolyte being 100%, the mass percentage of the second additive is 0.1%-0.5%.
[0013] Optionally, the electrolyte further includes a third additive, and the third additive includes one or more of adiponitrile, succinonitrile, 1,3,6-hexanetricarbonitrile, trans-hexenedinitrile, trans-butenenitrile, 1,2-bis(cyanoethoxy)ethane and 1,2,3-tris(cyanoethoxy)propane; Based on the total mass of the electrolyte being 100%, the mass percentage of the third additive is 2%-5%.
[0014] Optionally, the electrolyte further includes a fourth additive, and the fourth additive includes one or more of fluoroethylene carbonate, difluoroethylene carbonate, and trifluoromethylethylene carbonate; Based on the total mass of the electrolyte being 100%, the mass percentage of the fourth additive is 13%-18%.
[0015] The beneficial effects of the present invention are: The lithium-ion battery provided by the present invention comprises a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the positive electrode sheet comprises a solid electrolyte, and the electrolyte comprises a first additive; the first additive can form a protective film on the surface of the positive electrode sheet, reduce the side reaction between the electrolyte and the active substance in the positive electrode sheet and the solid electrolyte, and can effectively improve the high-temperature service life of the battery core; at the same time, adding a solid electrolyte of a corresponding particle size to the positive electrode sheet can provide a stable ion transmission path, and even at low temperatures, lithium ions can shuttle more smoothly between the positive electrode sheet and the electrolyte through the channel of the solid electrolyte, thereby reducing the polarization phenomenon caused by the obstruction of ion transmission; in addition, the present application adjusts the first additive, the solid electrolyte in the positive electrode sheet and the positive electrode material It was found that the lithium-ion battery meets the following conditions: when 1.25≤L / (D*S)≤5, the first additive can effectively protect the positive and negative electrodes and will not significantly deteriorate the positive electrode impedance and increase the electrolyte viscosity, the solid electrolyte maintains the structural stability and ion transmission channel of the positive electrode sheet, reduces the problem of decreased lithium ion transmission due to low temperature and does not significantly deteriorate the high temperature cycle performance of the battery cell; in summary, the lithium-ion battery provided in the present application provides a solid electrolyte, a first additive, and adjusts the relationship between the first additive, the solid electrolyte, and the median particle size D50 of the solid electrolyte in the positive electrode material layer, so that the lithium-ion battery can simultaneously take into account good low temperature discharge performance and high temperature cycle life. DETAILED DESCRIPTION
[0016] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0017] The present invention provides a lithium ion battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the positive electrode sheet comprises a positive electrode material layer, the positive electrode material layer comprises a positive electrode active material and a solid electrolyte, and the electrolyte comprises a first additive; The first additive comprises at least one of the following compounds: ; The lithium-ion battery meets the following conditions: 1.25≤L / (D*S)≤5; S% is the mass percentage of the first additive in the electrolyte; L% is the mass percentage of the solid electrolyte in the positive electrode material layer; Dμm is the median particle size D50 of the solid electrolyte in the positive electrode material layer.
[0018] Specifically, the lithium-ion battery provided by the present invention comprises a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the positive electrode sheet comprises a solid electrolyte, and the electrolyte comprises a first additive; the first additive can form a protective film on the surface of the positive electrode sheet, reduce the side reaction between the electrolyte and the active substance in the positive electrode sheet and the solid electrolyte, and can effectively improve the high-temperature service life of the battery core; at the same time, adding a solid electrolyte of corresponding particle size to the positive electrode sheet can provide a stable ion transmission path, and even at low temperatures, lithium ions can shuttle more smoothly between the positive electrode sheet and the electrolyte through the channel of the solid electrolyte, thereby reducing the polarization phenomenon caused by the obstruction of ion transmission; in addition, the present application adjusts the first additive, the solid electrolyte in the positive electrode sheet and the positive electrode The relationship between the median particle size D50 of the solid electrolyte in the material layer is found, and the lithium-ion battery meets the following conditions: when 1.25≤L / (D*S)≤5, the first additive can effectively protect the positive and negative electrodes and will not significantly deteriorate the positive electrode impedance and increase the electrolyte viscosity. The solid electrolyte maintains the structural stability and ion transmission channel of the positive electrode sheet, reduces the problem of decreased lithium ion transmission due to low temperature and does not significantly deteriorate the high-temperature cycle performance of the battery cell. In summary, the lithium-ion battery provided in the present application provides a solid electrolyte, a first additive, and adjusts the relationship between the first additive, the solid electrolyte, and the median particle size D50 of the solid electrolyte in the positive electrode material layer, so that the lithium-ion battery can simultaneously take into account good low-temperature discharge performance and high-temperature cycle life.
[0019] The first additive is a sulfate derivative. As the first additive, the sulfate group in its molecular structure has high chemical activity and can interact with various components in the battery. During the cycle of the battery, the sulfate derivative of the first additive forms a protective film on the surface of the positive electrode and the negative electrode to prevent certain components in the electrolyte (such as decomposition products of solvent molecules) from corroding the positive electrode material, thereby increasing the cycle life of the battery. In addition, the sulfate derivative of the first additive interacts with the active ingredients in the electrolyte to reduce the activity of the active ingredients, so that the chemical reaction inside the battery during storage is slower, thereby reducing the self-discharge rate and extending the storage time of the battery.
[0020] In some embodiments, the solid electrolyte includes one or more of lithium aluminum titanium phosphate, lithium lanthanum titanium oxide, and lithium lanthanum zirconium oxide.
[0021] Specifically, the crystal structure of the lithium aluminum titanium phosphate (LATP) provides a channel for lithium ion transmission, and its three-dimensional skeleton structure allows lithium ions to move relatively freely therein, which is beneficial to improving the ion transmission efficiency of the battery during the charging and discharging process; LATP has good chemical stability in the electrochemical environment of the battery, forms a relatively stable interface with the positive electrode material and the electrolyte, and can resist corrosion and decomposition reactions of the electrolyte in a high temperature environment.
[0022] Lithium lanthanum titanium oxide (LLTO) has high ionic conductivity. In high temperature environments, the titanium-oxygen chemical bonding in its crystal structure is conducive to the rapid conduction of lithium ions. During the high-temperature cycle of the battery, LLTO can provide an efficient ion transmission path, so that the internal resistance of the battery will not increase significantly due to temperature increase, thereby maintaining the good performance of the battery.
[0023] The cubic crystal structure of lithium lanthanum zirconium oxide (LLZO) provides a three-dimensional continuous transmission channel for lithium ions, which is not easily distorted when the high and low temperature environment of the battery changes. In low temperature environments, the crystal structure of LLZO can ensure the smooth flow of ion channels, allowing lithium ions to be transmitted normally, avoiding the obstruction of ion transmission caused by structural changes. In high temperature environments, LLZO can also maintain structural stability, resist electrolyte erosion and thermal decomposition reactions, and help improve the battery's cycle performance and storage performance.
[0024] In some embodiments, the mass percentage of the solid electrolyte in the positive electrode material layer is 0.5%-2%.
[0025] Specifically, the mass percentage of the solid electrolyte in the positive electrode material layer may be 0.5%, 1%, 1.5% or 2%.
[0026] In some embodiments, based on the total mass of the electrolyte being 100%, the mass percentage of the first additive is 1%-4%.
[0027] It should be noted that when the content of the first additive is too low, the content of the low-impedance CEI film generated on the positive electrode surface is limited, and the high-temperature performance and low-temperature discharge performance of the battery cell are not significantly improved; when the content of the first additive is too high, the viscosity of the electrolyte increases, thereby increasing the polarization effect of the electrolyte in a low-temperature environment and deteriorating the low-temperature performance of the electrolyte. The inventor of this application has previously verified that in this application, when the mass percentage of the first additive is 1%-4%, the first additive and the solid electrolyte in the fluorine positive electrode sheet work together to play a good synergistic role to improve the electrical performance of lithium-ion batteries in high and low temperature environments.
[0028] Specifically, the mass percentage of the first additive may be 1%, 2%, 3% or 4%, or any value within the above range.
[0029] In some embodiments, the median particle size D50 of the solid electrolyte in the positive electrode material layer is 0.4-0.7 μm.
[0030] Specifically, when the median particle size D50 of the solid electrolyte in the positive electrode material layer is in the range of 0.4-0.7 μm, the solid electrolyte particles can form relatively more ion transmission channels in the positive electrode sheet. Compared with particles with larger particle sizes, particles with smaller particle sizes can be distributed more densely in the same volume, so that lithium ions have more channels to choose for transmission.
[0031] Solid electrolyte particles with a particle size of 0.4-0.7μm are not prone to thermal expansion at high temperatures, which may lead to damage to the structure of the positive electrode sheet. Since there is a certain gap and mutual support between the particles, they can resist the volume change caused by high temperature to a certain extent. When the battery is working or stored at high temperature, the solid electrolyte particles can maintain their relative position and structural integrity in the positive electrode sheet, thereby ensuring the smooth flow of ion transmission channels and reducing the problems of battery capacity attenuation and impedance increase caused by high temperature.
[0032] In some embodiments, the electrolyte further comprises a lithium salt and an organic solvent; Based on the total mass of the electrolyte being 100%, the mass percentage of the lithium salt is 12%-18%; Taking the total mass of the electrolyte as 100%, the mass percentage of the organic solvent is 59.5%-71.9%.
[0033] The mass percentage of the organic solvent may be 60%, 62%, 63%, 65%, 70% or 71.9%.
[0034] Specifically, the mass percentage of the lithium salt is 12%, 13%, 14%, 15%, 16%, 17% or 18%.
[0035] In some embodiments, the lithium salt includes one or more of lithium hexafluorophosphate, lithium difluorophosphate, lithium tetrafluoroborate, lithium bisfluorooxalatoborate, lithium bisoxalatoborate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethylimide, lithium difluorooxalatophosphate, lithium perchlorate, and lithium nitrate.
[0036] Increasing the amount of lithium salt used will increase the viscosity of the electrolyte and deteriorate the low-temperature discharge performance of the battery, while using too little lithium salt will deteriorate the antioxidant performance of the electrolyte and reduce the service life of the battery cell in a high temperature environment. The embodiment of the present application optimizes the total mass of lithium salt in the electrolyte to enable the battery to have good rate performance.
[0037] In some embodiments, the organic solvent includes two or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl formate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate and ethyl difluoroacetate.
[0038] The present application adopts an organic solvent with a relatively low melting point and a relatively high dielectric constant, which can maintain a relatively low viscosity even at low temperatures, and can enable the battery to have good electrochemical performance at extremely low temperatures.
[0039] In some embodiments, the electrolyte further comprises a second additive, The electrolyte further includes a second additive, wherein the second additive includes one or more of n-butyl phosphoric anhydride, lithium tetrafluoroborate and lithium difluorophosphate; Based on the total mass of the electrolyte being 100%, the mass percentage of the second additive is 0.1%-0.5%; The electrolyte further includes a third additive, wherein the third additive includes one or more of adiponitrile, succinonitrile, 1,3,6-hexanetricarbonitrile, trans-hexenedinitrile, trans-butenedinitrile, 1,2-bis(cyanoethoxy)ethane and 1,2,3-tris(cyanoethoxy)propane; Based on the total mass of the electrolyte being 100%, the mass percentage of the third additive is 2%-5%; The electrolyte further includes a fourth additive, wherein the fourth additive includes one or more of fluoroethylene carbonate, difluoroethylene carbonate, and trifluoromethylethylene carbonate; Based on the total mass of the electrolyte being 100%, the mass percentage of the fourth additive is 13%-18%.
[0040] Specifically, the mass percentage of the second additive may be 0.1%, 0.2%, 0.3%, 0.4% or 0.5%; the mass percentage of the third additive may be 2%, 3%, 4% or 5%; the mass percentage of the fourth additive may be 13%, 14%, 15%, 16%, 17% or 18%.
[0041] Specifically, the second type of additives can form a low-impedance CEI at the positive electrode. If the added amount is small, the improvement will not be obvious, and if the content is high, negative effects such as insolubility or increased negative electrode impedance will occur; the third additive is a nitrile additive. Increasing the use of nitrile additives will worsen the impedance of the positive electrode of the battery and worsen the low-temperature discharge performance of the battery, while if the use of nitrile additives is too low, the protective effect on the positive electrode is not obvious, and high-temperature storage is prone to gas production, which is not conducive to the low-temperature cycle performance of the battery in low-temperature scenarios; the fourth additive can be fluoroethylene carbonate, which can form a stable and low-impedance SEI film at the negative electrode, reducing the consumption of nitrile compound additives, phosphoric anhydride additives and solvents at the negative electrode due to side reactions, thereby worsening the negative electrode impedance.
[0042] The inventors have verified through multiple experiments that the third additive, the fourth additive and the second additive can work synergistically to form a stable and low-impedance passivation layer at the positive and negative electrodes of lithium ions, and jointly promote lithium ions to achieve high-rate discharge and high-temperature long-cycle performance in low-temperature environments.
[0043] In some embodiments, the lithium-ion battery provided in the present application further includes a negative electrode sheet and a separator, wherein the separator is disposed between the positive electrode sheet and the negative electrode sheet, and during the battery charging and discharging process, active lithium ions are embedded or extracted back and forth between the positive electrode sheet and the negative electrode sheet.
[0044] The present application achieves high-rate long-cycle discharge of lithium-ion batteries in low-temperature environments while taking into account good high-temperature cycle and storage performance by optimizing the composition of the electrolyte and the composition of the positive electrode material in the positive electrode sheet; the first additive, the second additive, the third additive, and the fourth additive in the electrolyte are used in combination with the solid electrolyte in the positive electrode sheet to synergistically improve the problems of decreased electrolyte ion conductivity and severe electrode polarization when the battery is used in low temperature, so that the battery has low-temperature long-cycle performance and high-power discharge performance when used in low-temperature scenarios, and takes into account high-temperature cycle and storage performance.
[0045] In some embodiments, the positive electrode sheet, the negative electrode sheet and the separator can be made into an electrode assembly by a winding process or a lamination process.
[0046] Specifically, the lithium-ion battery provided by the present invention can be used for, but not limited to, mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, and energy storage systems.
[0047] In some embodiments, the positive electrode sheet includes a positive electrode current collector, the positive electrode active material is coated on the surface of the positive electrode current collector, and the positive electrode current collector is a conventional metal foil or a composite current collector, for example, aluminum foil.
[0048] In some embodiments, the positive electrode slurry includes the positive electrode active material, a conductive agent and a binder, and the positive electrode active material includes but is not limited to lithium iron phosphate, lithium iron manganese phosphate, lithium cobalt oxide, ternary LiNi x Co y Mn zOne or more of O2 materials (x+y+z=1, x≥y); the conductive agent includes but is not limited to at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers; the binder includes but is not limited to at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin.
[0049] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode material layer coated on the surface of the negative electrode current collector. The negative electrode current collector can be selected from a metal foil or a composite current collector, for example, can be selected from a copper foil.
[0050] In some embodiments, the negative electrode material layer includes a negative electrode active material, a binder and a conductive agent; the negative electrode active material includes but is not limited to one or more of graphite, hard carbon, silicon, silicon oxide compounds and silicon carbon compounds; the conductive agent includes but is not limited to one or more of conductive carbon black, acetylene black, Ketjen black, carbon dots, carbon nanotubes, graphene, carbon nanofibers, and superconducting carbon; the binder includes but is not limited to one or more of styrene-butadiene rubber, water-based acrylic resin, polyvinylidene fluoride, polytetrafluoroethylene, ethylene-vinyl acetate copolymer, polyacrylic acid, carboxymethyl cellulose, polyvinyl alcohol and polyvinyl butyral.
[0051] The diaphragm can be selected from a porous structure diaphragm with good chemical stability and mechanical stability. The material of the diaphragm can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The diaphragm can be a single-layer film or a multi-layer composite film without special restrictions. When the diaphragm is a multi-layer composite film, the materials of each layer can be the same or different without special restrictions.
[0052] The present invention is further described below by way of examples.
[0053] Table 1
[0054] Example 1 This embodiment is used to illustrate the lithium ion battery disclosed in the present invention, and includes the following operating steps: Preparation of positive electrode The positive electrode active material lithium cobalt oxide (LiCoO2), lithium aluminum titanium phosphate solid electrolyte (particle size D50 is 0.5 μm), conductive agent carbon black, binder polyvinylidene fluoride PVDF, and carbon nanotubes CNT are fully stirred and mixed in N-methylpyrrolidone solvent at a mass ratio of 97.7:0.5:0.5:0.9:0.4 to form a uniform positive electrode slurry; The positive electrode slurry is evenly coated on the positive electrode current collector Al foil, and then dried, rolled and compacted (the compaction density is 4.25g / cm 3 ) and other processes to obtain the positive electrode sheet.
[0055] Preparation of negative electrode The negative electrode active material graphite, silicon carbide, the binder styrene-butadiene rubber, and the thickener sodium carboxymethyl cellulose are fully stirred and mixed in a proper amount of deionized water solvent in a mass ratio of 92.5:5:2:0.5 to form a uniform negative electrode slurry; The negative electrode slurry is evenly coated on the negative electrode current collector copper foil, and then dried, rolled and compacted (the compaction density is 1.68g / cm 3 ) and other processes to obtain the negative electrode sheet.
[0056] Preparation of electrolyte Lithium salt: 13% lithium hexafluorophosphate (LiPF6) + 2% lithium bis(fluorosulfonyl)imide (LiFSI); The first additive: 1-2, 1%, the second additive: 0.2% lithium tetrafluoroborate, the third additive: 3% succinonitrile (SN), the fourth additive: 13% fluoroethylene carbonate (FEC); The solvent is equal to 100% minus the mass fraction of lithium salt and all additives added in the ratio of propylene carbonate to ethyl propionate = 1:3.
[0057] Preparation of lithium-ion batteries The positive electrode sheet, separator and negative electrode sheet are stacked in order, the stacked electrode sheet and separator are wound to obtain a core, the bare core is placed in the aluminum-plastic film formed by punching and forming, and the prepared electrolyte is injected into the baked and dried battery cell at an injection coefficient of 1.5g / Ah. After vacuum packaging, standing, formation and other processes, the preparation of the lithium-ion battery is completed.
[0058] Example 2-29 Examples 2-29 are used to illustrate the lithium ion battery disclosed in the present invention, including most of the operations in Example 1, except that: The type and content of the first additive and the second additive in Examples 2-29, and the type, amount and particle size of the solid electrolyte shall be based on the corresponding parameters in Table 1.
[0059] Comparative Example 1 This comparative example is used to compare and illustrate the lithium ion battery disclosed in the present invention, including most of the operations in Example 1, except that: The type and content of the first additive and the second additive, and the type, content and particle size of the solid electrolyte in Comparative Examples 1-8 shall be based on the corresponding parameters in Table 1.
[0060] Performance Testing The following performance tests were performed on Examples 1-29 and Comparative Examples 1-8 prepared as above: -20℃ rate discharge performance test: At 25℃, discharge the divided cells at 0.2C constant current to 2.7V and let it stand for 10 minutes. Charge them at constant current and constant voltage to 4.53V, with a cut-off current of 0.05C, and let it stand for 10 minutes. Discharge them at 0.2C constant current to 2.7V, record the discharge capacity as C1, and let it stand for 10 minutes. Charge them at 0.5C constant current and constant voltage to 90% C1 capacity, with a cut-off current of 0.05C, and let it stand for 3 hours at -20℃, then discharge them at 5W to 2.7V. If the valley voltage during the discharge process is not less than 3V, it is recorded as a "pass" test, otherwise it is recorded as a "failure" test.
[0061] 45℃ Cyclic Performance Test: After standing at 45℃ for 2h, the divided battery was discharged at 0.5C constant current to 2.7V, with a cut-off current of 0.05C; after standing for 10 minutes, it was then charged at 3C constant current and constant voltage to 4.53V, with a cut-off current of 0.05C, and then stood for 10 minutes, and discharged at 0.5C to 2.7V, and this cycle was repeated. The discharge capacity was recorded as the initial capacity. After 500 cycles at the same rate and the same charge and discharge method, the capacity retention rate of the battery after 500 cycles was calculated. The calculation formula is as follows. If the capacity retention rate is higher than 80%, it passes the test: The 500th cycle capacity retention rate (%) = (500th cycle discharge capacity / initial cycle discharge capacity) × 100%.
[0062] There are 5 batteries in each group, and the average capacity retention rate is recorded.
[0063] The test results obtained are entered in Table 2.
[0064] Table 2
[0065] It can be seen from the test results in Table 2 that the rate discharge performance and cycle performance of Examples 1-29 are better than those of Comparative Examples 1-8 as a whole. The reason is that the corresponding parameter settings in each component in Examples 1-29 satisfy 1.25≤L / (D*S)≤5, and the corresponding lithium ion batteries have good effects in the -20°C discharge valley voltage and 45°C cycle test, while the relevant parameters set in Comparative Examples 1-8 do not satisfy the relationship 1.25≤L / (D*S)≤5, resulting in poor performance of the lithium ion batteries prepared in the comparative examples. It can be seen that when the relationship between the first additive in the lithium ion battery, the solid electrolyte in the positive electrode sheet, and the median particle size D50 of the solid electrolyte satisfies 1.25≤L / (D*S)≤5, the battery cell can simultaneously have good low-temperature discharge performance and cycle performance; It can be seen from the test results of Examples 1-4 that an increase in the content of solid electrolyte is beneficial to improving the low-temperature rate discharge performance of the battery cell; it can be seen from the test results of Examples 4-8 and Comparative Example 7 that an increase in the content of the first additive is beneficial to improving the 45°C cycle capacity retention rate of the battery cell, but affects the low-temperature discharge of the battery cell, which may be due to the increase in the additive content and the increase in the viscosity of the electrolyte, and when the content of the first additive is higher than 4%, the high-temperature cycle performance of the battery cell is not significantly improved.
[0066] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A lithium ion battery, characterized in that: It includes a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the positive electrode sheet includes a positive electrode material layer, the positive electrode material layer includes a positive electrode active material and a solid electrolyte, and the electrolyte includes a first additive; The first additive comprises at least one of the following compounds: ; The lithium-ion battery meets the following conditions: 1.25≤L / (D*S)≤5; S% is the mass percentage of the first additive in the electrolyte; L% is the mass percentage of the solid electrolyte in the positive electrode material layer; Dμm is the median particle size D50 of the solid electrolyte in the positive electrode material layer.
2. A lithium ion battery according to claim 1, characterized in that: The solid electrolyte includes one or more of lithium aluminum titanium phosphate, lithium lanthanum titanium oxide and lithium lanthanum zirconium oxide.
3. A lithium ion battery according to claim 1, characterized in that: The mass percentage of the solid electrolyte in the positive electrode material layer is 0.5%-2%.
4. A lithium ion battery according to claim 1, characterized in that: Based on the total mass of the electrolyte being 100%, the mass percentage of the first additive is 1%-4%.
5. A lithium ion battery according to claim 1, characterized in that: The median particle size D50 of the solid electrolyte in the positive electrode material layer is 0.4-0.7 μm.
6. A lithium ion battery according to claim 1, characterized in that: The electrolyte also includes a lithium salt and an organic solvent; Based on the total mass of the electrolyte being 100%, the mass percentage of the lithium salt is 12%-18%; Taking the total mass of the electrolyte as 100%, the mass percentage of the organic solvent is 59.5%-71.9%.
7. A lithium ion battery according to claim 6, characterized in that: The lithium salt includes one or more of lithium hexafluorophosphate, lithium difluorophosphate, lithium tetrafluoroborate, lithium bisfluorooxalatoborate, lithium bisoxalatoborate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethylimide, lithium difluorooxalatophosphate, lithium perchlorate and lithium nitrate; and / or, The organic solvent includes two or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl formate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate and ethyl difluoroacetate.
8. A lithium ion battery according to claim 1, characterized in that: The electrolyte further includes a second additive, wherein the second additive includes one or more of n-butyl phosphoric anhydride, lithium tetrafluoroborate and lithium difluorophosphate; Based on the total mass of the electrolyte being 100%, the mass percentage of the second additive is 0.1%-0.5%.
9. A lithium ion battery according to claim 8, characterized in that: The electrolyte further includes a third additive, wherein the third additive includes one or more of adiponitrile, succinonitrile, 1,3,6-hexanetricarbonitrile, trans-hexenedinitrile, trans-butenedinitrile, 1,2-bis(cyanoethoxy)ethane and 1,2,3-tris(cyanoethoxy)propane; Based on the total mass of the electrolyte being 100%, the mass percentage of the third additive is 2%-5%.
10. A lithium ion battery according to claim 8, characterized in that: The electrolyte further includes a fourth additive, wherein the fourth additive includes one or more of fluoroethylene carbonate, difluoroethylene carbonate, and trifluoromethylethylene carbonate; Based on the total mass of the electrolyte being 100%, the mass percentage of the fourth additive is 13%-18%.
Citation Information
Patent Citations
Low-temperature-resistant lithium iron phosphate semi-solid battery as well as positive electrode slurry and preparation method thereof
CN117012957A
Positive plate and battery
CN118213470A
Lithium ion battery
CN118676373A
Electrolyte and lithium ion battery
CN118738559A
Lithium ion battery and preparation method thereof
CN119009172A
Cited By
Lithium ion battery and electric device
CN121282357A